The formation of low-dimensional ionic crystallites in carbon nanotubes - Wilson, M (2002)
Computer simulation models were constructed and applied to understand the low-dimensional crystallites formed in carbon nanotubes when filled with liquid KI. By using a much simplified model, the precise atomistic region of the specific distortions observed experimentally were determined. As a result, the same model was applied to understanding the actual atomistic mechanism by which these tubes fill. It was shown that the narrow pore radius of the nanotube, coupled with the ionic ordering inherent in the filling material, are critical in the formation of the low-dimension crystallites observed experimentally.